2017
DOI: 10.1111/jfd.12694
|View full text |Cite
|
Sign up to set email alerts
|

Are brown trout Salmo trutta fario and rainbow trout Oncorhynchus mykiss two of a kind? A comparative study of salmonids to temperature‐influenced Tetracapsuloides bryosalmonae infection

Abstract: Proliferative kidney disease (PKD) of salmonids caused by Tetracapsuloides bryosalmonae causes high mortalities of wild brown trout (Salmo trutta fario) and farmed rainbow trout (Oncorhynchus mykiss) at elevated water temperatures. Here the aim was to compare the temperature-dependent modulation of T. bryosalmonae in the two salmonid host species, which display different temperature optima. We used a novel experimental set-up in which we exposed brown trout and rainbow trout to an identical quantified low conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
(66 reference statements)
1
18
0
Order By: Relevance
“…Similarly, inhibition of il-1β has been previously reported in the kidney of brown trout infected with Tetracapsuloides bryosalmonae , the agent of proliferative kidney disease (PKD) [78], in the intestine infected with E. leei [79] or C. shasta , the agent of enteronecrosis or gut-rot disease in salmonids [32]. Low expression of ifnγ was previously reported in the kidney during the early stages of PKD (slightly increased by 50 dpi; [80]), while other myxozoan models suggest its increase and possible contribution to the cytotoxic activities [81, 82]. The timing of the downregulation of these genes is in accordance with the increasing expression of il-10 [83].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inhibition of il-1β has been previously reported in the kidney of brown trout infected with Tetracapsuloides bryosalmonae , the agent of proliferative kidney disease (PKD) [78], in the intestine infected with E. leei [79] or C. shasta , the agent of enteronecrosis or gut-rot disease in salmonids [32]. Low expression of ifnγ was previously reported in the kidney during the early stages of PKD (slightly increased by 50 dpi; [80]), while other myxozoan models suggest its increase and possible contribution to the cytotoxic activities [81, 82]. The timing of the downregulation of these genes is in accordance with the increasing expression of il-10 [83].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rainbow trout is often used as a model species for laboratory investigations of fish disease, including to reproduce PKD in controlled conditions [e.g., (14, 17, 18, 23, 3437)]. Though, rainbow trout and brown trout react differently to T. bryosalmonae infection, in terms of sensitivity to infectious agent and environmental stress (46), intensity of T. bryosalmonae infection (48), or temperature-dependant modulation of the parasite (49) for example. Therefore, some of the conclusions based on experiments with rainbow trout might not correspond to the situation of wild brown trout populations in their natural habitat with fluctuating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, elevated water temperatures have been suggested to exacerbate PKD infections and drive disease related mortality of wild brown trout ( Wahli et al, 2002 , 2007 ). Moreover, several lab and field studies have demonstrated the influence of temperature on host-parasite dynamics in the salmonid— T. bryosalmonae system ( Bettge et al, 2009a , 2009b ; Bailey et al, 2017 , 2018 ; Strepparava et al, 2017 ). However, given the strong interference of human activities with the diversity and functioning of freshwater ecosystems ( Søndergaard & Jeppesen, 2007 ; Vörösmarty et al, 2010 ; Dodds, Perkin & Gerken, 2013 ), PKD dynamics may not only be driven by temperature change, but by multiple stressors.…”
Section: Introductionmentioning
confidence: 99%